Applied Communication Strategy through Digital Signage for Social Care Management in Malang - Silvatri, Hapsari Dian; Megawati, Citra Dewi; Palevi, Bima Romadhon Parada Dian (Baca Dulu Publisher, 2025)
The rapid growth of digital technology has influenced communication strategies within social institutions that need to be more effective, interactive, and transparent. This study aims to apply a digital-based communication strategy through the implementation of digital signage as a medium for delivering information and education in social care institutions in Malang City. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings show that the application of digital signage enhances message delivery effectiveness, increases information accessibility, and strengthens the interaction between social institutions and the public. Furthermore, digital signage contributes to building the image of institutions as adaptive and innovative in facing technological advancements and communication challenges in the digital era. The implication of this research emphasizes that digital-based communication strategies can serve as an innovative solution to improve communication management, promote transparency, and support the operational effectiveness of social institutions.